Colorimetric determination of ambient ozone using indigo blue droplet - Felix, Erika P. [UNESP]; Cardoso, Arnaldo Alves [UNESP] (FapUNIFESP (SciELO), 2006)
A simple and sensitive method based on a liquid droplet is described for the measurement of atmospheric ozone. A 30 μL drop of indigo blue solution is suspended in a flowing-air sampling stream. The ozone collected reacts with the indigo solution resulting in its decolorization. The colorimetric sensor is composed of two optical fibers and the source of monochromatic light was a red LED (625 nm). The calibration curve was constructed with ozone standard concentrations ranging from 37 - 123 ppbv. The detection limit achieved was 7.3 ppbv. The method considered here showed itself to be easy to apply with a fast response and a total analysis time of only 5 minutes.

Um método simples e sensível, baseado em uma gota líquida, é descrito para medida do ozônio atmosférico. Uma gota de 30 µL de solução de índigo azul é suspensa em uma corrente de ar para amostragem. O ozônio coletado reage com a solução de índigo azul, provocando seu descoramento. O sensor colorimétrico é composto por duas fibras ópticas; a fonte de luz monocromática usada foi um LED vermelho (625 nm). A curva analítica foi construída com concentrações padrão de ozônio, na faixa de 37 a 123 ppbv. O limite de detecção alcançado foi 7,3 ppbv. O método considerado mostrou-se de fácil aplicação e resposta rápida, com um tempo total de análise de apenas 5 minutos.
Keywords: Colorimetric sensor; Liquid droplet; Optical fibers; Ozone